The Role of Parents in Preparing Balanced Menu with Children's Nutritional Status - Intan Fazrin; Katarina Kaka Daha; Kamaru lImron Musa (Journal Of Nursing Practice, 2022)
Background: Nutritional intake in children plays an important role in optimizing growth and development in children. The adequacy of nutritional intake in children can be assessed by the state of nutritional status characterized by thin, normal, and obese children. One of the roles of parents is to be responsible for fulfilling nutrition for their children. The desire of parents to fulfill their children's nutritional needs is often the background of inappropriate feeding practices. Inappropriate feeding practices include always fulfilling a child's desire to consume the food he wants, even many parents allow whatever food their child consumes, many parents serve ready-to-eat food Lack of nutritious food will lead to child growth retardation, the prevalence of malnutrition in 2013 was 19.6%, consisting of 5.7% malnutrition and 13.9% malnutrition. When compared with the national prevalence rate in 2010 (17.9%), it seems that this is increasing. Purpose: The aim of this study is to know the relationship between the role of parents in preparing a balanced menu with the nutritional status of children. Methods: The design used is a literature review, namely by using several journals from several sources such as: Google Scholar, PubMed. Nutritional Status, publication year between 2015-2020. Results: The results of the journal discussion show that there is an influence between the role of parents in preparing a balanced menu for children with the nutritional status of the child. Conclusion: It was concluded that the role of parents is really needed for the growth and development of the child.